Measurements of Total OH Reactivity During CalNex‐LA. Issue 11 (2nd June 2021) - Hansen, R. F.; Griffith, S. M.; Dusanter, S.; Gilman, J. B.; Graus, M.; Kuster, W. C.; Veres, P. R.; de Gouw, J. A.; Warneke, C.; Washenfelder, R. A.; Young, C. J.; Brown, S. S.; et al.
Abstract: Total OH reactivity was measured during the California Research at the Nexus of Air Quality and Climate Change field campaign at the Pasadena ground site using a turbulent flow tube reactor with laser‐induced fluorescence detection of the OH radical. Collocated measurements of volatile organic compounds (VOCs), inorganic species, and meteorological parameters were made and used to calculate the total OH reactivity, which was then compared to the measured values. An analysis of the OH reactivity measurements finds that although the measured reactivity correlated well with the calculated reactivity, the measurements were consistently greater than the calculations for all times during the day, with an average missing OH reactivity of 8–10 s −1, accounting for approximately 40% of the measured total OH reactivity. An analysis of correlations with both anthropogenic tracers of combustion and oxygenated VOCs as well as air trajectories during the campaign suggest that the missing OH reactivity was likely due to a combination of both unmeasured local emissions and unmeasured oxidation products transported to the site. Approximately 50% of the missing OH reactivity may have been due to emissions of unmeasured volatile chemical products, such as pesticides, cleaning agents, and personal care products. Key Points: Total OH reactivity measured during the CalNex‐LA field campaign was consistently greater than that calculated from measured OH sinks An analysis suggests that the missing reactivity is likely due to both unmeasured local emissions and unmeasured oxidation products Approximately 50% of the missing OH reactivity may have been due to emissions of unmeasured volatile chemical products